PENDAMPINGAN TRAINING MOTIVASI BERBASIS NILAI ISLAMI DALAM UPAYA MENINGKATKAN RASIO/PARTISIPASI PENDIDIKAN TINGGI DI INDONESIA STUDI SMKN 2 KOTA PARIAMAN - Ulinnas, Syifa; Irfanda, Hamzah (Institut Agama Islam Negeri Kerinci, 2026)
Participation in higher education in Indonesia remains a strategic issue, particularly among vocational high school graduates. This phenomenon is influenced by negative perceptions of bachelor's degree graduates, a strong work and migration orientation, and weak motivation to pursue knowledge. This activity aims to increase student motivation and awareness in continuing their education to higher education through Islamic values-based motivational training at SMKN 2 Pariaman City. The approach used was participatory and educational, using training methods, reflective discussions, higher education counseling, and internalization of Islamic values ​​regarding the importance of seeking knowledge. Data were collected through post-activity observations and participant reflections, then analyzed descriptively and qualitatively. The results showed an increase in student understanding of the urgency of higher education, a change in perceptions of the academic world, and increased motivation and interest in continuing their studies to higher education. Islamic values-based mentoring has proven effective in building academic awareness and future orientation in students, thus contributing positively to efforts to increase participation in higher education. Keywords: Motivation Training, Islamic Values, Higher Education